The identification of Belus with Cronus in Nonnus’s Dionysiaca 18.222-8 - Garstad, Benjamin (My University, 2003)
There is an instance of Belus being identified with Cronus in the Dionysiaca of Nonnus of Panopolis (5th c.), but it has not heretofore been recognized. In the eighteenth book Dionysus visits the Assyrian king, Staphylus, who encourages the god by telling him a story of the Titanomachy and the monsters sent against Zeus. 'Assyrian Belus' is mentioned at the beginning of this story, though all modern editors, following Cunaeus have rearranged the introductory lines in various ways, but consistently so as to make Belus the grandfather of Staphylus and the original narrator of the story. The character of Belus is treated inconsistently in the rest of the epic, in book 3 Belus, referred to as 'the Libyan Zeus', is the son of Poseidon and Libya, and the grandfather of Cadmus\ but in book 40 Belus is treated as the Assyrian name for the Sun as a god (Cronus and Zeus are said to be other names of the Sun). Reference to these passages cannot, therefore, help us toward a proper reading of Belus in book 18, but does demonstrate that in Nonnus 'Belus' refers to no single character, neither human nor divine.
Keywords: Cunaeus; Belus; Cronus; Dionysiaca; Nonnus of Panopolis; Staphylus; Titanomachy; Zeus